Recycling of Triplets into Singlets for High‐Performance Organic Lasers. Issue 1 (23rd October 2021) - Senevirathne, Chathuranganie A. M.; Yoshida, Seiya; Auffray, Morgan; Yahiro, Masayuki; Karunathilaka, Buddhika S. B.; Bencheikh, Fatima; Goushi, Kenichi; Sandanayaka, Atula S. D.; Matsushima, Toshinori; Adachi, Chihaya
Abstract: Achieving continuous‐wave (CW) lasing in organic semiconductors is known to be a difficult task because long‐lived triplets quench radiative singlets via singlet–triplet annihilation (STA). To avoid STA and operate organic lasers in CW or long‐pulse photoexcitation, the triplets need to be removed from an organic laser gain medium. However, this triplet removal leads to a loss of excitons. In addition to removing the detrimental triplets, here it is reported a triplet recycling process, which includes triplet scavenging and successive triplet upconversion via triplet–triplet annihilation (TTA) to regenerate emissive singlet excitons in a laser medium. An anthracene derivative of 9‐(1‐naphthalenyl)‐10‐(4‐(2‐naphthalenyl)phenyl)anthracene (NaNaP‐A) and a laser dye of 4, 4′‐bis[4‐(diphenylamino)styryl]biphenyl (BDAVBi) are used as the triplet recycling sensitizer and the emitting laser dye, respectively. In this laser system, NaNaP‐A can efficiently scavenge the triplets formed on BDAVBi because the triplet level is deeper for NaNaP‐A than for BDAVBi, and then NaNaP‐A successively recycles the triplets into the BDAVBi's singlet state via TTA. The TTA compensates and overcomes the STA in this laser system. Hence, these laser devices can be operated with long pulse widths of up to 10 ms. This unique triplet recycling behavior is confirmed by transient photoluminescence (PL) and electroluminescence (EL) studies. Abstract : Long‐pulse lasing is difficult to realize in organics because of quenching of singlets by triplets. In this study, triplets are scavenged to suppress the singlet quenching and then recycle triplets via triplet–triplet annihilation (TTA) to produce singlets. Long‐pulse lasing from organics with the triplet scavenging and recycling processes is demonstrated.